Comparative Chloroplast Genomics and Phylogenetic Analysis of Zygophyllum (Zygophyllaceae) of China - Zhang, Ling; Wang, Shu; Su, Chun; Harris, AJ; Zhao, Liang; Su, Na; Wang, Jun-Ru; Duan, Lei; Chang, Zhao-Yang (Frontiers in Plant Science, 2021)
The genus Zygophyllum comprises over 150 species within the plant family Zygophyllaceae. These species predominantly grow in arid and semi-arid areas and about 20 are endemic to the northwestern China. In this study, we sampled 24 individuals of Zygophyllum representing 17 species and sequenced their complete chloroplast (cp) genomes. For comparison, we also sequenced chloroplast genomes of two species of Peganum from China representing the closely allied family, Nitrariaceae. The 24 cp genomes of Zygophyllum ranged in size from 104,221 to 106,286 bp, each containing a large single-copy (LSC) region (79,245-80,439 bp), a small single-copy (SSC) region (16,285-17,146 bp), and a pair of inverted repeat (IR) regions (3,792-4,466 bp). These cp genomes contained 120-121 genes each, including 83-84 protein-coding genes (PCGs), four ribosomal RNA genes, and 33 transfer RNA genes, and all cp genomes showed similar gene order, content and structure. However, the SC and IR regions had greater similarity within genera than between Zygophyllum and Peganum. We detected nine highly variable intergenic spacers: matK-trnQ, psaC-rps15, psbZ-trnG, rps7-trnL, rps15-trnN, trnE-trnT, trnL-rpl32, trnQ-psb and trnS-trnG. Additionally, we identified 156 simple sequence repeat (cpSSR) markers shared among the genomes of the 24 Zygophyllum samples and seven cpSSRs that were unique to the species of Zygophyllum. These markers may be useful in future studies on genetic diversity and relationships of Zygophyllum and closely related taxa. Using the sequenced cp genomes, we reconstructed a phylogeny that strongly supported the division of Chinese Zygophyllum into herbaceous and shrubby clades. We utilized our phylogenetic results along with prior morphological studies to address several remaining taxonomic questions within Zygophyllum. Specifically, we found that Z. kaschgaricum is best regarded as a variety of Z. xanthoxylon and show support for the present treatment of the former genus Sarcozygium as a subgenus within Zygophyllum. Our results provide a foundation for future research on the genetic resources of Zygophyllum.